2018 International Conference on Information and Communications Technology (ICOIACT) 2018
DOI: 10.1109/icoiact.2018.8350759
|View full text |Cite
|
Sign up to set email alerts
|

An analysis and a comparative study of cryptographic algorithms used on the Internet of Things (IoT) based on avalanche effect

Abstract: The doctor's office was always open for consultations whenever I had problems or questions regarding my experiments, results or research. Finally, I must submit my gratitude to my wife, Mrs. Tinswalo Audry Mabasa Muthavhine and to my children (Frankie Muthavhine, Lulama Muthavhine, Mukoni Muthavhine and Khuliso Muthavhine) for giving me the necessary support and constant motivation throughout my research and studies. This achievement would not have been successful without them. Thank you very much.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
(99 reference statements)
7
26
0
1
Order By: Relevance
“…Muthavhine and Sumbwanyambe [21] indicated that IoT devices were substantially tiny in size and memory allocation. Algorithms like AES were generically rejected due to memory constraints required before installation.…”
Section: Related Worǩmentioning
confidence: 99%
See 1 more Smart Citation
“…Muthavhine and Sumbwanyambe [21] indicated that IoT devices were substantially tiny in size and memory allocation. Algorithms like AES were generically rejected due to memory constraints required before installation.…”
Section: Related Worǩmentioning
confidence: 99%
“…Security and memory are the main concerns on IoT devices [1] - [7], [21]. The security of information, data, and network should be equipped with a strong cryptographic algorithm like Advanced Encryption Standard (AES) on each IoT devices to achieve identification of users, the confidentiality of data, integrity (correctness) of exact information, and deniability of unauthorized users including connection of unwanted devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini menggunakan Avalanche Effect sebagai alat ukur untuk mengevaluasi model super enkripsi yang diusulkan. Pengukuran dalam avalanche effect dilakukan dengan melihat setiap perubahan bit yang terjadi dalam data tersandi yang diakibatkan oleh perubahan yang dilakukan terhadap data awal maupun kunci, dalam avalanche effect semakin banyak perubahan bit maka semakin baik model tersebut [15]- [17]. Proses yang terdapat dalam avalanche effect dapat dilihat pada Persamaan (3).…”
Section: Pengujian Model Kriptografiunclassified
“…IoT devices and platforms are advancing boundless while initiating a seamless combination of computer networks with things or objects [1,2]. IoT is an open network platform and a new communication standard for the latest innovations, connecting multiple heterogeneous devices to render new conventional services [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, new services provided by IoT devices have to be sufficiently secured utilizing solid cryptographic algorithms such as AES [1,2]. A cryptographic algorithm is a mathematical method that converts plaintext (simple messages) into ciphertext (unclear messages), and vice versa [5,6].…”
Section: Introductionmentioning
confidence: 99%